PEMANFAATAN LIMBAH NANAS UNTUK PEMBUATAN KOMPOS MENGGUNAKAN KOMPOSTER ROTARY DRUM - sriharti sriharti (Purifikasi, 2007)
The objective of this experiment was to utilize solid waste from a pineapple juice processing factory Lipisari in Subang as compost raw material. Another objective was to create an efficient composting unit facility. The composting process was carried out in a rotary drum composting unit made from wood. The frame was made from iron St 37. The composting facility had cylindrical shape with a length of 1.958 m, diameter of 1.198 m. I had a capacity of 2 m3 or 600 kg. It was equipped with an agitator and a blower of 14 inch diameter, 150 watt and 220 volt capacity. It was rotated by a 2 HP electrical motor. The composting process was accelerated by the application of EM4 activator. Results of this research showed that the composting process occurred within 7 days. The compost quality meets the Indonesian National Standard, SNI No. 19-7-30-2004.